Transcatheter tricuspid valve‐in‐valve implantation for degenerated surgical bioprosthesis. Issue 2 (8th January 2023) - Chen, Jinmiao; Yang, Ye; Song, Wenyu; Feng, Deguang; Yan, Yang; Wang, Chunsheng; Wei, Lai
Abstract: Background: Isolated redo surgery for degenerated tricuspid bioprosthesis is of very high risk. We aimed to evaluate the safety and efficacy of transcatheter valve‐in‐valve (TVIV) implantation using a novel balloon expandable Renato valve. Methods: A prospective multicenter study was conducted to enroll patients with degenerated tricuspid bioprostheses. A total of 12 patients underwent TVIV implantation using the Renato valve system via transfemoral, transjugular, or transatrial approaches at three institutions from May 2021 to October 2021. All‐cause mortality and hemodynamic performance were evaluated up to 6 months after procedure. Results: The median age was 68.2 years, and 75.0% were female. Six patients had a history of rheumatic left‐sided valve surgery and late tricuspid valve replacement. The median preoperative Society of Thoracic Surgeons score was 9.9%. The procedures were successful in all cases. Tricuspid regurgitation and paravalvular leak were none or mild in all patients. The median transvalvular gradient decreased from 7.8 mmHg preoperatively to 4.5 mmHg at 6 months after TVIV, respectively. No death occurred and all patients recovered to New York Heart Association functional class I or II during a 6‐month follow‐up. Conclusions: TVIV implantation with the Renato valve was a safe and effective treatment for degenerated bioprostheses in high‐risk patients.